Developing a guide to climate & health justice education: Process and content - Mita Huq; Sonora English; Heizal Patricia Nagginda; Jon Bonifacio; Thilagawathi Abi Deivanayagam; Rita Issa; Sorcha Ni Chobhthaigh; Priscila de Morais Sato; Hans Mulindwa; Delan Devakumar (Elsevier, 2023)
Climate justice and health education can address the disproportionate health impacts of climate change on minoritized communities by providing frameworks to build awareness and instigate action on climate-related health inequities. The Envisioning Environmental Equity Educator's Guide to Climate and Health Justice provides a framework for educators, activists and health professionals to lead lessons on health and climate justice that center the experiences of those Most Affected People and Areas (MAPA) by climate change. Collaborators in Brazil, the Philippines, and Uganda engaged in stakeholder meetings to assess priorities and needs about climate and health with policymakers, doctors, activists, and students. These meetings informed the product: An educator's guide to climate and health justice that explores their dynamics from an anti-racist, anti-colonial approach. The guide serves as a recommended lesson framework fit with concepts, examples, and activities for educators teaching in primary and secondary learning settings. It is an innovative climate and health justice educational resource that draws on principles of anti-colonialism, critical thinking and consciousness, and engaged pedagogy. It offers a strategy for climate justice communication that targets diverse audiences across climate, health and social contexts by promoting educational approaches that center MAPA experiences, fit for diverse audiences.